Meningkatkan Imunitas Di Tengah Pandemi Covid-19 Melalui Program Makassar Recover Ecosystem - Wina Ayu Giswanti; Ika Riswanti Putri; Retno Sunu Astuti; Teuku Afrizal (PERSPEKTIF, 2022)
During this pandemic Covid-19, health is the main thing in preventing the infection of this virus. With the new normal conditions, then the community can reactivate. However, the limited information, especially in maintaining and improving the body's immunity, is needed socialization in the people of Makassar city will be the importance of immunity in this pandemic period. Makassar city as the capital of South Sulawesi Province is also affected by this pandemic condition. Awareness, and discipline of citizens related to the dangers of this pandemic is still very minimal, can be seen from the behavior of every citizen who does not wear a mask and keep a distance. Makassar Recover Ecosystem program involves volunteers, community leaders, and the entire community of Makassar City. Makassar Recover Ecosystem program aims to provide vitamins for free so that the body's immunity is maintained so that it can fight the attack of the Covid 19 virus. This immunity strengthening activity through the target time span to be achieved by measuring the success rate through evaluations that will be carried out every two weeks. There are three factors that will be the first reference, the decrease in positivity rate below one digit to the lowest point, namely, zero percent, second, decrease in the number of people exposed, third, all Makassar entrances have been installed Genose enough or other means of examination that will be done PCR and Swab become the core of the examination to ensure negative positive from the examination. Strengthening immunity activities will take place according to the results obtained. That is, it will be a permanent activity until it is declared completely free of the virus as well as an affirmation from the World Health Organization and governments that the pandemic is over.